A Heterozygous Variant of TGFB3 in a Patient With an Atypical Presentation of Loeys–Dietz Syndrome: A Case Report - Tarika D. Patel; Meagan N. McNicholas; Christina M. Laukaitis (Annals of Internal Medicine: Clinical Cases)
Loeys–Dietz syndrome (LDS) 5 is characterized by aortic aneurysms, hypertelorism, and cleft palate/bifid uvula. We describe a woman with a transforming growth factor beta3 (TGFβ3) mutation who displays a forme fruste phenotype of LDS5. A 43-year-old woman with joint pain and hypermobile joints underwent evaluation for hypermobile Ehlers–Danlos syndrome. Her features included pes planus, treated high-arched palate, and increased joint mobility. Genetic analysis identified a pathogenic TGFβ3 variant (c.427A>T, p.Arg143*), clarifying the diagnosis of LDS5. Comparing our patient with others with TGFB3 mutations illustrated the diversity of LDS5 features, often a milder forme fruste form, which warrants more investigation due to insufficient characterization.